2005
DOI: 10.1256/qj.04.65
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of cloud droplets in a turbulent cloud‐chamber flow

Abstract: SUMMARYWe present the results of a laboratory study of the spatial distribution of cloud droplets in a turbulent environment. An artificial, weakly turbulent cloud, consisting of droplets of diameter around 14 μm, is observed in a laboratory chamber. Droplets on a vertical cross-section through the cloud interior are imaged using laser sheet photography. Images are digitized and numerically processed in order to retrieve droplet positions in a vertical plane. The spatial distribution of droplets in the range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
(19 reference statements)
0
12
0
Order By: Relevance
“…Nevertheless, droplet counts in cumulus clouds have been analysed to quantify the departure from a Poisson distribution. A number of techniques have been developed to quantify this departure, including the Fishing test (Baker, 1992), clustering index , pair-correlation function and its volume average (Kostinski and Shaw, 2001;Shaw et al, 2002;Lehmann et al, 2007), analysis of power spectra Khain, 2001, 2003) and analysis of correlations (Jaczewski and Malinowski, 2005). Mathematically, these techniques are related to each other (Shaw et al, 2002;Baker and Lawson, 2010) but there remains some debate over the merits of each test when applied to real data.…”
Section: Observations Of Cloud Dropletsmentioning
confidence: 99%
“…Nevertheless, droplet counts in cumulus clouds have been analysed to quantify the departure from a Poisson distribution. A number of techniques have been developed to quantify this departure, including the Fishing test (Baker, 1992), clustering index , pair-correlation function and its volume average (Kostinski and Shaw, 2001;Shaw et al, 2002;Lehmann et al, 2007), analysis of power spectra Khain, 2001, 2003) and analysis of correlations (Jaczewski and Malinowski, 2005). Mathematically, these techniques are related to each other (Shaw et al, 2002;Baker and Lawson, 2010) but there remains some debate over the merits of each test when applied to real data.…”
Section: Observations Of Cloud Dropletsmentioning
confidence: 99%
“…The dynamics of inertial particles [1][2][3][4][5][6] in fluid flows have been studied intensively in the last decade (for a review see [7,8]), and it has been shown to have important effects in many situations of practical interest ranging from atmospheric sciences [9][10][11][12] to oceanography [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Though some improvement has been achieved by including the effect of entrainment [3] of dry air inside the cloud, such a mechanism can only partially justify the presence of a wide range of droplet sizes, as it concerns only the cloud boundaries, whereas the spreading of size distribution is measured in adiabatic cloud cores as well. Other mechanisms have been proposed to explain such a property of the inner part of the cloud: the effect of stochastic fluctuations in the vapour field has been considered in [4], as well as in [5,6] where droplet reaction on the vapour field is responsible for its local fluctuations. The effects of developed turbulence have been first 2 A.…”
Section: Introductionmentioning
confidence: 99%